Synchronous melanomas: one on tattoo and one on healthy skin - Francesco Ricci; Gianluca Pistore; Giovanni Di Lella; Luca Fania; Siavash Rahimi; Cristina Fortes; Annarita Panebianco; Damiano Abeni (Dermatology Reports, 2025)
Tattooing is a widespread practice among the population, particularly among young people. With the increased popularity of tattoos, there have also been several reports of acute and chronic adverse events after tattooing. Malignant melanoma cases arising from tattoos have been increasingly described; however, there is no clear relationship between this practice and tumorigenesis. We present a case of two synchronous melanomas (one located on a decorative tattoo) and update the literature.